Kazantzakis, Volume 1 : Politics of the Spirit - Bien, Peter (Book collections on Project MUSE., 2012)
""No author who lives in Greece, "" writes Peter Bien, ""can avoid politics."" This first volume of his major intellectual biography of Nikos Kazantzakis approaches the distinguished--and controversial--writer by describing his struggle with political questions that were in reality aspects of a fervent religious search. Beginning with Kazantzakis's early career in fin-de-siecle Paris and his discovery of William James, Nietzsche, and Bergson, the book continues by describing his experiments with communism in turbulent Greece, his visits to Soviet Russia, and the publication of his epi.